Massive open online courses for continuing professional development of GPs. Issue 9 (September 2020) - Player, Emily; Shiner, Alice; Steel, Nick; Rodrigues, Veena
Continuing professional development (CPD) is essential for the maintenance and improvement of the knowledge and skills of healthcare professionals. GP registrars are required to evidence CPD in their ePortfolio and likewise, GPs are mandated to accrue and evidence a minimum of 50 hours CPD for their annual appraisal. CPD can be delivered in many ways, with an increasing movement towards online learning. Technology-enhanced learning (TEL) encompasses online learning and is ever changing. This article will discuss a type of TEL known as massive open online courses (MOOCs) and the role of MOOCs in delivering CPD.